2011
DOI: 10.1016/j.nbt.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Cellulase production in a new mutant strain of Penicillium decumbens ML-017 by solid state fermentation with rice bran

Abstract: To produce cellulolytic enzyme efficiently, Penicillium decumbens strain L-06 was used to prepare mutants with ethyl methane sulfonate (EMS) and UV-irradiation. A mutant strain ML-017 is shown to have a higher cellulase activity than others. Box-Behnken's design (BBD) and response surface methodology (RSM) were adopted to optimize the conditions of cellulase (filter paper activity, FPA) production in strain ML-017 by solid-state fermentation (SSF) with rice bran as the substrate. And the result shows that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
1
14
2
1
Order By: Relevance
“…RCK 2010, encontrando maior atividade enzimática em pH 5,5 e 30 °C, sendo este resultado dez vezes inferior ao encontrado no presente estudo. Resultado semelhante (pH 5,7 e 30 °C) foi observado por Liu et al (2011), na produção de celulases por Penicillium decumbens ML-017.…”
Section: Figura 1 -Efeito Estimado Do Ph E Da Temperatura Na Produçãounclassified
“…RCK 2010, encontrando maior atividade enzimática em pH 5,5 e 30 °C, sendo este resultado dez vezes inferior ao encontrado no presente estudo. Resultado semelhante (pH 5,7 e 30 °C) foi observado por Liu et al (2011), na produção de celulases por Penicillium decumbens ML-017.…”
Section: Figura 1 -Efeito Estimado Do Ph E Da Temperatura Na Produçãounclassified
“…62 A high yield (159.1 U/g) of β-glucosidase was achieved from rice bran-based SSF by the Penicillium citrinum fungus. 40 Also, Liu et al 63 optimized the conditions of cellulase production by Penicillium decumbens in SSF using rice bran as the substrate and obtained 5.76 IU/g, whereas Lee et al 64 used rice bran in combination with yeast extract to produce the same enzyme in SmF by Bacillus subtilis and 196.8 U/mL was obtained. Different agro-industrial residues were used for the production of this vital enzyme such as enzymatically treated wheat bran which exhibited 1.1 U/mL of the cellulase enzyme under SmF by Aspergillus flavus , 65 or untreated corn cob which produced 5.25 IU/mL under SmF by Trichoderma reesei.…”
Section: Cereal Biorefinery Waste Valorizationmentioning
confidence: 99%
“…Many studies reported that several Penicillium species secrete a complete cellulase with high β-glucosidase activity (Singh et al, 2009;Dillon et al, 2011;Liu et al, 2011;Singhvi et al, 2011;Castro et al, 2010;Dutta et al, 2008). Cellulase from Penicillium funiculosum exhibited better-balanced β-glucosidase, endo-and exoglucanase activities than commercial preparations had done (Castro et al, 2010), and produced glucose faster during corn cob hydrolysis than commercialized enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Penicillium citrinum produced alkali-tolerant and thermostable cellulases (Dutta et al, 2008). In order to improve the production rate and specific activity of cellulases, chemical and physical mutagenesis have been applied to several fungal strains (Dillon et al, 2011;Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation